2018
DOI: 10.1590/1678-4162-10239
|View full text |Cite
|
Sign up to set email alerts
|

Partial internal hemipelvectomy as rescue therapy in obstipation in four dogs: case report

Abstract: Multiple pelvic fractures can lead to narrowing of the pelvic canal and loss of life quality. Hemipelvectomy, characterized by removal of bone fragments from the pelvis, is considered a rescue therapy. This report describes the technique of caudal partial hemipelvectomy in four cases of obstipation secondary to traumatic pelvic canal narrowing in four dogs, with promising results. All patients had tenesmus and fecal retention. After the procedure, the patients presented immediate normochezia and support of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…To widen the narrowed pelvic canal, techniques such as triple pelvic osteotomy, external (concurrent limb amputation), or internal (limb preservation) hemipelvectomy can be used (COSTA et al, 2018). In this case, we chose mid-to-caudal partial hemipelvectomy due to the severe trauma associated with the femur, which differed from the other cases in this study since a polypropylene mesh was not required for pelvic wall closure.…”
Section: Resultsmentioning
confidence: 99%
“…To widen the narrowed pelvic canal, techniques such as triple pelvic osteotomy, external (concurrent limb amputation), or internal (limb preservation) hemipelvectomy can be used (COSTA et al, 2018). In this case, we chose mid-to-caudal partial hemipelvectomy due to the severe trauma associated with the femur, which differed from the other cases in this study since a polypropylene mesh was not required for pelvic wall closure.…”
Section: Resultsmentioning
confidence: 99%
“…Hemipelvectomy for the treatment of pelvic fracture and malunion has also been successfully reported. [9][10][11] One study reported the removal of varying amounts of the pubis, ischium, acetabulum and ilium to manage pelvic canal stenosis following malunion of pelvic fractures. 9 One dog in this study had bilateral pubis and ischium removal without removal of the ipsilateral hindlimb.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic narrowing >45-50% (respectively, in cats and dogs) potentially could still be a risk for malunion or pelvic canal narrowing that can result in constant or intermittent constipation after conservative treatment [ 7 , 12 , 19 , 35 , 36 ]. Intermittent constipation has been reported in two cats in Group 2.…”
Section: Discussionmentioning
confidence: 99%